El uso de las herramientas digitales y la psicomotricidad en los niños de 4 a 5 años - Chicaiza Bolaños, Erika Viviana (2022)
The research problem arose with the observation of a deficient use of digital tools by teachers during the transition of education to the virtual modality, which limits to get full advantage of the wide range of resources offered by the digital world, as well as the lack of stimulation of parents at home, affecting the proper psychomotor development of children. This research is so important since its purpose is to make the educational community aware of the responsibility of both parents and teachers to be a continuous part of the teaching-learning process during the virtual modality. Hence, this research aims to determine the use of digital tools concerning the development of psychomotor development of children from 4 to 5 years old to identify the difficulties that arise during the learning process. The research methodology has a qualitative approach and has the appropriate theory. Conceptual references are necessary for its development; therefore, the collection of information was carried out through field research, taking 54 objects of study as a sample. We proceeded to apply the interviews to the three early education teachers and the authority as well as surveys of 25 parents and the observation form applied to 25 children of the initial sublevel II of the Naciones Unidas Basic Education School in order to know the influence of digital tools applied during the virtual meetings and their contribution to psychomotor development. The results of this research were analyzed and interpreted, arriving at to deduce that teachers should innovate the resources they use for the teaching-learning process because the teachers during the virtual modality have made exclusive use of the Zoom, Teams, and YouTube platforms, causing that children have little interest in virtual meetings. So it is recommended an adequate training and innovation of digital resources be a regular part of the educational process, not only when it is an imposition in front of different circumstances.